I'll Try That, Too - A Field Experiment in Retailing on the Effect of Variety During Display Promotions - Mareike Sachse; Sebastian Oetzel; Daniel Klapper (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
The effect of variety on consumer choice has been studied extensively, with some stream of literature showing the positive effects on choice and others arguing that too many alternatives may result in negative consequences (i.e., choice deferral or no purchase at all), often referred to as choice overload. In a field experiment with a major chocolate brand conducted at a German retail chain, we test for variety during a price and display promotion. Participating stores either include the full variety of products on the display or a reduced selection (low variety). Contrary to the literature on choice overload, we find a significantly positive effect of the display promotion on unit sales, which is stronger for stores with high variety. Further findings show a stronger promotion uplift for less popular products in stores with high variety on the display. This suggests that more variety may increase consumers' willingness to try new products, when the financial risk is low. We also test for the effect of product distribution on displays by analysing the number of facings. Additionally, we introduce an approach to determine an optimal space allocation of products on the display. Our findings suggest that an even distribution results in the highest profits for the retailer. We contribute to the literature on variety for consumer choices by offering insights from actual purchases with store-level scanner data of display promotions.
Keywords: M31; Marketing; C23; C93; D12; 330; variety; retailing; in-store display; field experiment